2018
DOI: 10.7717/peerj.5143
|View full text |Cite
|
Sign up to set email alerts
|

Short-term deleterious effects of standard isolation and cultivation methods on new tropical freshwater microalgae strains

Abstract: Algae with potential biotechnological applications in different industries are commonly isolated from the environment in order to obtain pure (axenic) stocks that can be safely stored for long periods of time. To obtain axenic cultures, antibiotics are frequently employed, and cryopreservation is applied to preserve standing stocks. However, many of these now standard methods were developed using strains derived from pristine to near-pristine environments and cold to temperate regions. The potential effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…According to their findings, little or no cryoprotection was observed when these CPAs were used alone. Aray-Andrade et al (2018) found DMSO–sucrose and glycerol to be effective cryoprotective agents while working with the cryopreservation of two Chlorella and one Scenedesmus species [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to their findings, little or no cryoprotection was observed when these CPAs were used alone. Aray-Andrade et al (2018) found DMSO–sucrose and glycerol to be effective cryoprotective agents while working with the cryopreservation of two Chlorella and one Scenedesmus species [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adequate concentration of nutrients can favor the physiological processes of the cell to counteract the damaging effects of cryopreservation, allowing its optimization through the formation of aldose type monosaccharides, which increases the osmolarity of the solution, causing cellular dehydration. These aldoses in synergy with cryoprotectors, minimize the damage of intracellular ice by increasing the total concentration of the solute and reducing the amount of ice formed in the cell (Bui et al, 2013;Aray-Andrade et al, 2018).…”
Section: Post-thawing Cell Viabilitymentioning
confidence: 99%
“…Cryopreservation is a biotechnological technique to preserve cell structures or biological material at low temperatures, which inactivates physiological processes for a period of time (Day and Brand, 2005;Smith et al, 2008;Bui et al, 2013;Saadaoui et al, 2016). Cryopreservation optimizes production, maintenance, and genetic stability of microalgae (Day and Brand, 2005;Bui et al, 2013;Aray-Andrade et al, 2018). The main challenge in cryopreservation is to develop techniques to guarantee post-thawing cell viability.…”
Section: Introductionmentioning
confidence: 99%